Down regulation of a heavy metal transporter gene influences several domestication traits and grain Fe-Zn content in rice. (November 2018) - Kappara, Saivishnupriya; Neelamraju, Sarla; Ramanan, Rajeshwari
Highlights: We identified two alleles of a heavy metal transporter gene OsHMA7. Overexpression of 261 allele increased grain Fe & Zn but decreased yield. Knockdown of OsHMA7 dramatically influenced several domestication-related traits. Foliar spray improved yield and grain Fe-Zn in OsHMA7 -knockdown rice. OsHMA7 has potential to improve rice production and biofortification. Abstract: Biofortification of rice ( Oryza sativa L.) would alleviate iron and zinc deficiencies in the target populations. We identified two alleles 261 and 284 of a Gramineae-specific heavy metal transporter gene OsHMA7 by analyzing expression patterns and sequences of genes within QTLs for high Fe & Zn, in Madhukar x Swarna recombinant inbred lines (RILs) with high (HL) or low (LL) grain Fe & Zn. Overexpression of 261 allele increased grain Fe and Zn but most of the transgenic plants either did not survive or did not yield enough seeds and could not be further characterized. Knocking down expression of OsHMA7 by RNAi silencing of endogenous gene resulted in plants with altered domestication traits such as plant height, tiller number, panicle size and architecture, grain color, shape, size, grain shattering, heading date and increased sensitivity to Fe and Zn deficiency. However, overexpression of 284 allele resulted in transgenic lines with either high grain Fe & Zn content (HL-ox) and tolerance to Fe and Zn deficiency or low grain Fe & Zn content (LL-ox) and phenotype similar to RNAi-lines. OsHMA7 transcript levels were five-fold higher in the HL-ox plants whereas LL-ox and RNAi plants showed 2–3 fold reduced levels compared to Kitaake control. Spraying LL-ox and RNAi lines with Fe & Zn at grain filling stage resulted in increased grain yield, significant increase in Fe & Zn content and brown pericarp. Altered expression of OsHMA7 influenced transcript levels of iron-responsive genes indicating cellular Fe-Zn homeostasis and also several domestication-related genes in rice. Our study shows that a novel heavy metal transporter gene influences yield and grain Fe & Zn content and has potential to improve rice production and biofortification.